2015
DOI: 10.14393/bj-v31n2a2015-27837
|View full text |Cite
|
Sign up to set email alerts
|

Influence of non carious cervical lesions depth, loading point application and restoration on stress distribution pattern in lower premolars: a 2D finite element analysis

Abstract: ABSTRACT:The aim of this study was to analyze the biomechanical behavior of lower premolars regarding the non-carious cervical lesion (NCCL) depth, load type and restoration status, using finite element analysis. Twodimensional virtual model simulating a healthy lower premolar were created using the CAD software. Based on this image, five models were generated: healthy (H), three types of NCCLs: small lesion (SL -0.5 mm deep), medium lesion (ML -1.0 mm), deep lesion (DL -1.5 mm), and restored lesion (RL). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 34 publications
(44 reference statements)
0
9
0
Order By: Relevance
“…In non-carious cervical lesions, there is a loss of tooth structure in the cervical region of the teeth, which can cause damage to aesthetics and hypersensitivity, as reported by Telles et al 2 and Nascimento et al 8 . The dentinal tubules can be exposed as a result of enamel loss by friction, abrasion, erosion or abfraction, generating a short, sharp pain that arises from the exposed dentin in response to stimuli 16 . This fact corroborates the present study, in which, in relation to the aspects that were analyzed, it can be seen that of the students who presented dentinal hypersensitivity, only one did not have a non-carious cervical lesion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In non-carious cervical lesions, there is a loss of tooth structure in the cervical region of the teeth, which can cause damage to aesthetics and hypersensitivity, as reported by Telles et al 2 and Nascimento et al 8 . The dentinal tubules can be exposed as a result of enamel loss by friction, abrasion, erosion or abfraction, generating a short, sharp pain that arises from the exposed dentin in response to stimuli 16 . This fact corroborates the present study, in which, in relation to the aspects that were analyzed, it can be seen that of the students who presented dentinal hypersensitivity, only one did not have a non-carious cervical lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies have reported that the position of the occlusal load modifies the intensity of stress concentration in the cervical regions. Loads applied obliquely along the long axis of the tooth can promote an increase in stress in the cervical region and are related to the formation and progression of NCCLs 16 . Also, the presence of traumatic dental occlusion is considered an important factor in the occurrence of these injuries 13 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The buccal load (BL) and palatal load (PL) were applied at 45 degrees to the long axis on buccal and palatal cusps respectively, simulating occlusal interferences (Rees 2002). The models were constrained to the side and base of cortical and trabecular bones to prevent displacement (Zeola et al 2015;Machado et al 2017).…”
Section: Peres Ts Et Almentioning
confidence: 99%